2007
DOI: 10.1186/1477-3163-6-16
|View full text |Cite
|
Sign up to set email alerts
|

RKIP does not contribute to MAP kinase pathway silencing in the Merkel Cell Carcinoma cell line UISO

Abstract: BackgroundThe Raf kinase inhibitor protein (RKIP) has been shown to block MAP kinase pathway as well as NFκB signalling. By means of immunohistochemistry, we previously demonstrated that the MAP kinase pathway is virtually inactive in Merkel cell carcinoma (MCC). Similarly to MCC in situ high RKIP expression accompanies absence of ERK phosphorylation in the MCC cell line UISO suggesting that RKIP might be causative for MAP kinase pathway silencing.MethodsApplying an siRNA approach RKIP expression was knocked d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The lack of ERK phosphorylation was always accompanied by a strong expression of the Raf kinase inhibitor protein (RKIP), a negative regulator of the MAPK cascade. However, silencing of RKIP did not lead to an induction of ERK phosphorylation [31]. The general inactivity of the "mitogenic" cascade distinguishes MCC from many other tumors such as melanoma and raises the question if active MAP kinase signaling is perhaps even a negative selection factor for MCC cells.…”
Section: Pathogenesismentioning
confidence: 98%
“…The lack of ERK phosphorylation was always accompanied by a strong expression of the Raf kinase inhibitor protein (RKIP), a negative regulator of the MAPK cascade. However, silencing of RKIP did not lead to an induction of ERK phosphorylation [31]. The general inactivity of the "mitogenic" cascade distinguishes MCC from many other tumors such as melanoma and raises the question if active MAP kinase signaling is perhaps even a negative selection factor for MCC cells.…”
Section: Pathogenesismentioning
confidence: 98%
“…In addition, RKIP overexpression in C4-2B cells led to reduced cell invasion in vitro. Interestingly, a Merkel carcinoma line was identified that overexpressed RKIP and lost ERK signaling; however, further studies revealed that RKIP depletion did not rescue the ERK signaling defect consistent with RKIP's role as a modulator rather than suppressor of the MAPK pathway [34]. Finally, a recent study showed that Snail, a mediator of the epithelial-mesenchymal transition (EMT), can inhibit RKIP transcription and negatively correlates with RKIP levels in tumors, consistent with a role for RKIP in metastasis [35].…”
mentioning
confidence: 99%
“…Furthermore, the expression levels of NF-κB were negatively correlated with those of RKIP. Several mechanisms might be invoked to explain how RKIP could regulate the occurrence and development of DN, including RKIP coupling with NF-κB-inducing kinase, TGF-D-activated kinase 1, I-κB kinase, and I-κB kinase β, which are all involved in inhibition of NF-κB signal transduction (Yeung et al, 2001;Corbit et al, 2003;Lorenz et al, 2003;Houben et al, 2007;Matallanas et al, 2011;Fujimori et al, 2012). Downregulation of RKIP might trigger the NF-κB pathway in DN, which then activates the I-κB kinase.…”
Section: Discussionmentioning
confidence: 99%